Workshop Digital Talent Perakitan dan Optimasi PC untuk Pemberdayaan Masyarakat Pati di Era Digital - Anin Maftukhah; Muhammad Atiq; Danang Hendrawan; Raka Dian Mahardi; Muhammad Reyhan F (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2026)
The rapid development of the digital era requires human resources to not only master software, but also understand hardware infrastructure. This community service program aims to improve the technical competence and digital literacy of the people of Pati Regency through a PC assembly and optimization workshop. The method used is the Participatory Action Learning Sistem (PALS), in collaboration with